UTILIZATION OF CHATGPT IN THE CONTEXT OF TAX EDUCATION IN INDONESIA: A PERSPECTIVE REVIEW - Raden Roro Fatmasari; Anggun Yolistina; Nazhira Nindya Padma Hanuun (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2023)
The rapid advancement of technology has paved the way for innovative approaches in various fields, including education. This study explores the potential applications of ChatGPT, a language generation model, in the context of tax education in Indonesia. The objective is to provide a comprehensive perspective on the feasibility and effectiveness of integrating ChatGPT into the tax education landscape. The research delves into the current state of tax education in Indonesia and identifies existing challenges. It then evaluates the capabilities of ChatGPT to address these challenges by offering personalized, interactive, and accessible learning experiences. The study considers the perspectives of educators, students, and tax professionals to gauge the reception and impact of ChatGPT in enhancing tax education. Furthermore, the research investigates the technical aspects of implementing ChatGPT, including customization for the Indonesian tax system, linguistic considerations, and ethical implications. By conducting a thorough examination, this study aims to contribute valuable insights for educators, policymakers, and technologists interested in leveraging advanced language models to improve the quality of tax education. In conclusion, this review sheds light on the potential benefits and considerations associated with integrating ChatGPT into tax education in Indonesia. It serves as a foundation for further research and discussions on the optimal utilization of artificial intelligence in educational contexts, particularly in the complex domain of taxation.